Upaya meningkatkan aktifitas dan hasil belajar matematika peserta didik dengan penggunaan mind map melalui pembelajaran kooperatif tipe STAD di kelas VIII SMP negeri 1 - Jumriah Jumriah (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2018)
Abstract This research is a classroom action research that aims to determine the increase in learning outcomes and student activities using the concept map (mind mapp) type STAD cooperative learning. This research was conducted at Cimahi 1 Public Middle School class VIIIA. The research method used was the classroom action research method, sampling using purposed random sampling. The results of the study were found 1. From the learning outcomes data, it was found that the average test scores of students in the first cycle were 64.4 (with learning completeness 44.45%), cycle II was 75.7 (with learning completeness 70.37 %), the third cycle is 81.4 (learning completeness is 88.9%). 2. While the data from the research results obtained that the average activity desired (On Task) students in the first cycle is 40%, cycle II is 71% and in the third cycle is 85%. The average activity that is not desired (Off Task) students in the first cycle is 60%, cycle II is 29% and cycle III is 15%. This data shows that the use of concept maps through STAD type cooperative learning is able to increase the desired activities (On Task) of students (an increase of 45%).